The role of Islamic economics in improving social and economic welfare - Jannah, Firdiyatul; Masrohatin, Siti; Anggitaningsih, Retna (Journal of Islamic Economy, 2025)
This study aims to analyze the role of sharia economics in improving social and economic welfare through the Systematic Literature Review (SLR) approach. This method is carried out in a structured manner to collect, evaluate, and analyze literature relevant to the research topic. The first stage is to formulate research questions regarding the contribution of sharia economics in poverty alleviation and financial inclusion. Literature was collected from scientific databases such as Google Scholar, Scopus, and ScienceDirect with keywords related to sharia economics and social welfare. Literature selection is carried out based on inclusion and exclusion criteria to ensure quality and relevance. The data obtained was analyzed using a thematic analysis method, grouping the findings into main themes such as the role of zakat, Islamic banking, and the impact of waqf on the community's economy. Validation is carried out using the Critical Appraisal Skills Programme (CASP) tool to ensure the quality of the articles analyzed. The results of the study show that sharia economics plays a significant role in improving social and economic welfare with the principles of social justice, sustainability, and social responsibility. Instruments such as zakat, waqf, infaq, and alms contribute greatly to community empowerment and the reduction of economic disparities. However, the development of the Islamic economy still faces challenges such as lack of understanding, inadequate regulations, and competition with conventional economic systems. Therefore, education, regulatory improvement, and integration with the global market are needed to maximize the benefits of the sharia economy.